Selfies as Social Movements: Influences on Participation and Perceived Impact on Stereotypes - Liu, Fannie; Ford Robinson, Denae; Dabbish, Laura; Parnin, Chris (In proceedings of the ACM Conference on Computer Supported Cooperative Work and Social Computing (CSCW), 2018)
A new kind of online movement has emerged on social media: identity hashtag movements, through which individuals share "selfies" and personal stories to elucidate the experiences of marginalized social groups. These movements have the potential to counteract bias and enable social justice, but are enacted in a forum rife with identity and boundary management concerns. To understand this type of movement, we present a qualitative study of #ILookLikeAnEngineer, a hashtag created to challenge engineering stereotypes. We interviewed 32 people, including participants and non-participants of the movement, about their experiences with the hashtag. We found that personally identifiable participation promoted feelings of empowerment and strengthened connections within the marginalized community. At the same time, the personal and professional identity focus raised ambiguity about the boundaries of the collective and the movement's ability to change stereotypes. We discuss implications for online collective action and the use of social media for addressing stereotypes.